Соглашение o международной дорожной перевозке опасных грузов (ДОПОГ 2025): Действует с 1 января 2025 года - United Nations Economic Commission for Europe (United Nations, 2025)
The Agreement concerning the International Carriage of Dangerous Goods by Road (ADR) is intended to increase the safety of international transport of dangerous goods by road. Its annexes are regularly amended and updated. They contain the conditions under which dangerous goods may be carried internationally. This revised version is based on amendments that will apply from 1 January 2025. It contains new or revised provisions, including new provisions for: the use of battery electric vehicles in vehicle category FL and the use of vehicles powered by hydrogen fuel cell and hydrogen powered vehicles as AT and FL vehicles; the carriage in bulk of molten aluminium; the carriage of waste in packagings; and the carriage in bulk of waste containing asbestos.